The Caci Dance as an art-based communication in instilling collective cultural values - Parani, Rizaldi; Purba, Herman; Hubner, Ira Brunchilda; Juliana, Juliana (Faculty of Communications Science, Dr. Soetomo University, 2025)
The Caci Dance culture from East Nusa Tenggara, Indonesia, is a cultural performing art and is basically a form of war dance performed by the younger generation based on the principles of brotherhood and mutual respect as a form of gratitude. The purpose of this research is to analyse how the Caci Dance as a form of art-based communication instils the meaning of collective cultural values for the Manggarai people in Flores. This research uses a qualitative approach and ethnographic methods. Primary data was obtained through in-depth semi-structured interviews with several stakeholders such as traditional village heads, religious leaders and the government. The findings from this study are that Caci dance as a performance art also has an entertainment function in addition to conveying social messages. In the Caci Dance, the message to be conveyed, apart from providing entertainment through dance and musical performances, is also related to moral encouragement to pay more attention to sustainable efforts in preserving the Earth we inhabit. On the other hand, the Caci Dance depicts the cultural values of collectivity held by the Manggarai community which can also describe the characteristics of the community. The collective values believed by the Manggarai community as their characteristics are the values of unity and mutual respect which are also seen from the process of involvement as an effort to preserve the Caci Dance.